Short term outcome of epileptic Seizure in children attending at Paediatric Neuroscience Department of Dhaka Shishu Hospital (Northern International Medical College Journal, 2020)
Background : The optimal response to antiepileptic treatment is the control of seizures. In different studies, it has been shown that childhood epilepsy presents with a variable course, and approximately one-third of epilepsy experience alternating relapse and remission. Some of them do not become seizure-free, despite adequate treatment.Objectives : This study aimed to see the short-term outcome of seizures in children with epilepsy (whether the seizure is controlled or not) and to correlate them with different predictors like socio-demographic factors, associated comorbidities, and adherence with antiepileptic drugs.Methods : This retrospective observational study was conducted in an Epilepsy Clinic of Paediatric Neuroscience Department of Dhaka Shishu Hospital (DSH) over a period of 3 years from January 2013 to December 2015. During this period 1-year follow-up record of each patient was analyzed. Information on bio demographic data, clinical and developmental assessment done by a multidisciplinary team was analyzed.Results : A total of 100 children who had epilepsy were included in this study. Unfavorable outcome (uncontrolled seizure) was found in children